On Tariffs v. Subsidies in Interstate Trade: A Legal and Economic Analysis - Christopher R. Drahozal (Washington University Law Quarterly, 1996)
Part II of this Article sets out the Supreme Court's current legal analysis of tariffs versus subsidies under the dormant Commerce Clause. Part III undertakes an economic analysis of tariffs versus subsidies, from both a traditional international economics perspective and from a rent-seeking perspective. Part IV suggests an alternative constitutional basis for the Court's distinction between tariffs and subsidies: the Import-Export Clause of the United States Constitution. Part V summarizes my conclusions.
Keywords: Interstate commerce clause (Constitutional law); Subsidies; Tariff – Law & amp; legislation